2020
DOI: 10.1080/13854046.2020.1806359
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric neuropsychological evaluation via telehealth: Novel models of care

Abstract: Objective: As the coronavirus pandemic extends across the globe, the impacts have been felt across domains of industry. Neuropsychology services are no exception. Methods for neuropsychological assessments, which typically require an in-person visit, must be modified in order to adhere to social distancing and isolation standards enacted in an effort to slow the pandemic. How can providers continue to meet the needs of patients referred for neuropsychology evaluations, while respecting federal and state guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 12 publications
1
34
0
Order By: Relevance
“…Institutions must consider cultural and health disparities, as the majority of the population can access electronic devices, but the assumption that everyone owns a device that is adequate for telehealth is false. For example, an emailed survey to parents of scheduled or waitlisted pediatric neuropsychology patients (N ¼ 222, 26% response rate) suggested that although 94% of respondents were interested in a telehealth appointment, only 74% of those owned either a desktop or laptop computer with a camera (Pritchard et al, 2020). The ability to reach a larger and more remote patient population is possible with teleNP; however, as clinicians and researchers begin to explore the opportunities this technology offers, its limitations must be identified and respected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Institutions must consider cultural and health disparities, as the majority of the population can access electronic devices, but the assumption that everyone owns a device that is adequate for telehealth is false. For example, an emailed survey to parents of scheduled or waitlisted pediatric neuropsychology patients (N ¼ 222, 26% response rate) suggested that although 94% of respondents were interested in a telehealth appointment, only 74% of those owned either a desktop or laptop computer with a camera (Pritchard et al, 2020). The ability to reach a larger and more remote patient population is possible with teleNP; however, as clinicians and researchers begin to explore the opportunities this technology offers, its limitations must be identified and respected.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a clinical interview and review of records can serve as an intervention in itself but can also be useful in accurately triaging testing cases. Practice models for triage and decision-making are described elsewhere in this issue (Hewitt & Loring, 2020;Pritchard et al, 2020).…”
Section: Approach To Servicementioning
confidence: 99%
See 1 more Smart Citation
“…As pediatric neuropsychologists at an academic medical center, we are concerned with how to best serve our medically and neurodevelopmentally complex patients during this unprecedented time. While our colleagues (Pritchard et al, 2020; this issue) present a novel three-tiered pediatric tele-neuropsychology service model, applying this modelfor complex medical and neurodevelopmental patients requires that clinicians engage in careful clinical decision-making. Thus, the current manuscript serves as a companion to Pritchard et al (2020) and illustrates the practical application of the model through clinical cases.…”
Section: Introductionmentioning
confidence: 99%
“…While our colleagues (Pritchard et al, 2020; this issue) present a novel three-tiered pediatric tele-neuropsychology service model, applying this modelfor complex medical and neurodevelopmental patients requires that clinicians engage in careful clinical decision-making. Thus, the current manuscript serves as a companion to Pritchard et al (2020) and illustrates the practical application of the model through clinical cases. In the case presentations below, we identify specific service options and service decision points within the model.…”
Section: Introductionmentioning
confidence: 99%